Dereplication and Quantification of Major Compounds of Convolvulus arvensis L. Extracts and Assessment of Their Effect on LPS-Activated J774 Macrophages - Hafiz Abdul Khaliq; Sergio Ortiz; Mireille Alhouayek; Giulio G. Muccioli; Joëlle Quetin-Leclercq (Molecules, 2022)
Convolvulus arvensis is used in Pakistani traditional medicine to treat inflammation-related disorders. Its anti-inflammatory potential was evaluated on hexane, dichloromethane, ethyl acetate, methanol, and aqueous extracts of whole plant on pro-inflammatory mediators in LPS-activated murine macrophage J774 cells at the non-cytotoxic concentration of 50 µg/mL. Ethyl acetate (ARE) and methanol (ARM) extracts significantly decreased mRNA levels of IL-6, TNF-α, MCP-1, COX-2, and iNOS. Furthermore, both extracts dose dependently decreased IL-6, TNF-α, and MCP-1 secretion. Forty-five compounds were putatively identified in ARE and ARM by dereplication (using HPLC-UV-HRMSn analysis and molecular networking), most of them are reported for the first time in C. arvensis, as for example, nineteen phenolic derivatives. Rutin, kaempferol-3-O-rutinoside, chlorogenic acid, 3,5-di-O-caffeoylquinic acid, N-trans-p-coumaroyl-tyramine, and N-trans-feruloyl-tyramine were main constituents identified and quantified by HPLC-PDA in ARE and ARM. Furthermore, chlorogenic acid, tyramine derivatives, and the mixture of the six identified major compounds significantly decreased IL-6 secretion by LPS-activated J774 cells. The activity of N-trans-p-coumaroyl-tyramine is shown here for the first time. Our results indicate that ARE, ARM and major constituents significantly inhibited the expression of pro-inflammatory mediators, which supports the use of this plant to treat inflammatory diseases.